Analysis of differential proteins in two different wing‐types of female Nilaparvata lugens. Issue 3 (27th November 2017) - Liang, An‐Wen; Liu, Ting‐Ting; Liang, Zi‐Qiang; Wang, Fang‐Hai
Abstract: Nilaparvata lugens (stal) is a rice pest and contains long‐winged and short‐winged varieties, called the wing differentiation. This study compared the protein profiles of the two wing‐types in females and two wing‐disc types 5th‐instar females by two‐dimensional electrophoresis analysis. We detected 172 and 174 protein spots in adults and 5th‐instar nymphs, respectively. The number of proteins with higher content in the long‐winged (disc) individuals is much more than that in the short‐winged (disc) individuals. A total of 32 differential protein spots were found, of which 20 were successfully identified. Their main function is about catabolic process, fiber and nucleoside binding, and they constitute 52 protein–protein interactions, which is around the glycolysis as the core. These results enrich the research on the protein Level in wing development, and provide more references for future studies.